Subscribing to diverse subjects in different classes: language development dichotomy - Bulelwa Makena; Bunmi Isaiah Omodan (Journal of Research on English and Language Learning (J-REaLL), 2022)
Language teachers, yet on the other side, language enhancement is compromised for learners whose home language is not English. Further than that, for teachers lacking specialisation of other subjects allocated to them, besides English language teaching and learning becomes a monotonous activity that does not inspire learner attitudes more so that the greatest percentage of subjects underpinning the curriculum is offered in an English medium. This paper aims to explore if offering different subjects in varying classes has any significant impact on language development. The study is located within interpretivist paradigm using qualitative research appraoch and case study research design. 5 secondary school English language teachers were purposefully nominated and interviewed to study the problem’s complex phenomenon. Findings divulged that multi subject allocation in the site investigated seemed to be compromising subject specification, thus leading to a decline in enhancing language development. The study recommends that to re-build teacher and learner motivation, policies should be put in place to consider subject speciality when allocation of subjects is administered.